2009
DOI: 10.1007/dcr.0b013e31819ef76b
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carcinoembriogenic Antigen in Predicting Response and Survival to Neoadjuvant Chemoradiotherapy for Distal Rectal Cancer

Abstract: A postchemoradiotherapy CEA level <5 ng/ml is a favorable prognostic factor for rectal cancer and is associated with increased rates of earlier disease staging and complete tumor regression. Postchemoradiotherapy CEA levels may be useful in decision making for patients who may be candidates for alterative treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 26 publications
4
65
3
8
Order By: Relevance
“…Habr-Gama, fue la primera cirujano en determinar prospectivamente, el manejo no quirúrgico de pacientes con cáncer localmente avanzado de recto, después de determinarse respuesta clínica completa posterior a la neoadyuvancia 19,[23][24][35][36][37][38][39] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Habr-Gama, fue la primera cirujano en determinar prospectivamente, el manejo no quirúrgico de pacientes con cáncer localmente avanzado de recto, después de determinarse respuesta clínica completa posterior a la neoadyuvancia 19,[23][24][35][36][37][38][39] .…”
Section: Discussionunclassified
“…Aunque la sensibilidad en fumadores es equívoca 39 , se ha considerado como factor pronóstico de sobrevida en algunos estudios. También se ha sugerido, el aumento de intensidad de la quimioterapia adyuvante, cuando los valores de ACE preneoadyuvancia son marcadamente elevados 40 .…”
Section: Discussionunclassified
“…predictive values, the results were controversial. Perez et al didn′t find a correlation between initial CEA-pre level and pCR (37).…”
Section: Serum Carcinoembryonic Antigen (Cea)mentioning
confidence: 94%
“…Perez et al reported that a CEA-post level < 5 ng/mL was associated with increased rates of clinical CR and pCR (37). CEA-post with a different cut-off value of 2.7 ng/mL was also proved to be an independent predictor of good tumor regression (p = 0.001) (38).…”
Section: Serum Carcinoembryonic Antigen (Cea)mentioning
confidence: 99%
See 1 more Smart Citation